Persepsi Mahasiswa Penerima Beasiswa KIP-Kuliah terhadap Pengelolaan Keuangan Pribadi - Yohana Muko Kaha; Viktorianus Delsapto Negar (Trending: Jurnal Manajemen dan Ekonomi, 2026)
The Indonesia Smart College Card Program (KIP-Kuliah) is one of the government’s initiatives to expand access to higher education for students from low-income families. However, the program’s effectiveness does not solely depend on the amount of financial assistance provided, but also on the students’ ability to manage their personal finances wisely. This study aims to describe the perceptions of KIP-Kuliah scholarship recipients regarding their personal financial management. The research employed a descriptive quantitative approach, with a population of 461 recipients from the 2021 to 2024 cohorts. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in 83 respondents. Although questionnaires were distributed to 150 students, only 83 were returned and considered valid for analysis. Data were collected using an online Likert-scale questionnaire covering aspects of budgeting, record keeping, financial control, and financial awareness. The data were analyzed using descriptive statistics focusing on mean scores and response percentages. The findings indicate that students’ perceptions of personal financial management fall under the “Good” category (average score = 3.95 or 79%). Most students demonstrate positive financial awareness, particularly in allocating scholarship funds for academic needs and saving for future purposes. However, weaknesses remain in budgeting practices and maintaining records of expenses. In conclusion, although the financial awareness of KIP-Kuliah recipients is relatively good, continuous financial literacy education is still necessary to improve effective and sustainable scholarship fund management.